Christ's Body Keeps the Score: Trauma-Informed Theology and the Neuroscience of PTSD - Hill, Preston (TheoLogica: An International Journal for Philosophy of Religion and Philosophical Theology, 2023)
Recent findings in neuroscience and psychology indicate that “the body keeps the score” of PTSD. Concurrently, trauma-informed theology to date has deployed pneumatology to explain how God experiences trauma in the Christian narrative of salvation. Yet, in Christian theology the divine person of the Holy Spirit has no assumed human body. This raises an important question as to whether a body is needed for God to keep the score of posttraumatic stress in a manner consistent with neuroscience and how this might shape one’s account of trauma in Christian soteriology. In this article, I take an analytic science-engaged approach to assess the viability of dominant proposals in trauma-informed theology which deploy trauma theory to assert God’s experience of trauma and explain this experience with exclusive reference to pneumatology. After reviewing clinical and scientific research on the neuroscience of PTSD which has been neglected in these approaches, I argue that Christology is a more obviously fitting locus for suggesting God’s experience of trauma within Christian soteriology than the person of the Holy Spirit. I conclude that since the body keeps the score of trauma from a scientific perspective, Christ’s body keeps the score of trauma from a science-engaged theology perspective.